Examining on Indonesian Legal Challenges for Future Transnational Healthcare Service - Kusuma, Febrian Indar Surya; Hermawan, Sapto (Faculty of Law, Universitas Brawijaya, 2020)
Facing the fourth industrial revolution, the state must strengthen its role to protect its citizens as a part of its efforts to provide social security. Indonesia as a nation also have to face this challenge, especially on the ability to provide healthcare and medication for their citizen neither they lived in the country nor stay overseas. This kind of issue has to be our concern because of our current situation in the globalization era force us to eliminate the national border and start to design transnational services to fulfill our basic needs. Therefore, this paper will conduct research that focuses on the healthcare and medication services in the South East Asia, especially a comparison between Malaysia and Indonesia’s government. Furthermore, this study will also give a brief preview of the 4.0 industrial revolution that brings the shifting of a new era for fulfilling a necessary healthcare service by using transnational big data. Through a social justice perspective and sociological law approach, the researcher uses social security theory that will lead us to reach the concept of the welfare state. This comparison will give us a larger image to see Indonesian government legal challenges and opportunities to provide a new form of healthcare services.